Floral Paintings in the central band of the Pillar - Temples of India Project Team (Jio Institute, 2024)
View of the pilaster from the east-facing elevation of the temple. These pilasters are slightly different from the pillars on the other side of the temple. Though the base and the shaft of the pillar are the same, the brackets are different. Also, these pillars are painted in white with multicolour floral motifs.